The role of saltwater and waves in continental shelf formation with seaward migrating clinoform - Iwasaki, Toshiki (Proc Natl Acad Sci U S A, 2020)
Continental shelves have generally been interpreted as drowned coastal plains associated with the allogenic effect of sea-level variation. Here, without disputing this mechanism we describe an alternative autogenic mechanism for subaqueous shelf formation, driven by the presence of dissolved salt in seawater and surface waves. We use a numerical model describing flow hydrodynamics, sediment transport, and morphodynamics in order to do this. More specifically, we focus on two major aspects: 1) the role of saltwater in the subaqueous construction of continental shelves and 2) the transformation of these shelves into seaward-migrating clinoforms under the condition of repeated pulses of water and sediment input and steady wave effects, but no allogenic forcing such as sea-level change. In the case for which the receiving basin contains fresh water of the same density as the sediment-laden river water, the hyperpycnal river water plunges to form a turbidity current that can run out to deep water. In the case for which the receiving basin contains sea water but the river contains sediment-laden fresh water, the hypopycnal river water forms a surface plume that deposits sediment proximally. This proximate proto-shelf can then grow to wave base, after which wave-supported turbidity currents can extend it seaward. The feature we refer to is synonymous with near-shore mud belts.